Underwater Drone: Aset Militer, Perangkat Penelitian dan Kedaulatan - Akbar Kurnia Putra; Afrilia Faradilla; Bernard Sipahutar (Fakultas Hukum Universitas Bangka Belitung, 2021)
This article aims to analyze the regulation of the use of underwater drones in international law from the perspective of Indonesian law. This article concludes that the regulation regarding the use of underwater drones that cross national borders has not been specifically regulated both in international law and in national law. Therefore, it is necessary to make special arrangements regarding the use of underwater missiles in terms of attack, spying, and collecting marine data so that foreign countries do not freely operate underwater drones in the territorial sea of ​​other countries and do not violate the right of peaceful passage as regulated. in UNCLOS 1982. In the future, the government needs to strengthen the maritime security system in Indonesian territory and take firm action against persons involved in the entry of foreign military assets into Indonesian territory. Key Words: International Law, UNCLOS 1982, Underwater Drone